2014
DOI: 10.14786/flr.v2i1.37
|View full text |Cite
|
Sign up to set email alerts
|

How we use what we learn in Math: An integrative account of the development of commutativity.

Abstract: One crucial issue in mathematics development is how children come to spontaneously apply arithmetical principles (e.g. commutativity). According to expertise research, well-integrated conceptual and procedural knowledge is required. Here, we report a method composed of two independent tasks that assessed in an unobtrusive manner the spontaneous use of procedural and conceptual knowledge about commutativity. This allowed us to ask (1)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 64 publications
2
15
0
Order By: Relevance
“…On the one hand, this result suggests that our approximation task is not suitable to boost the integration of both knowledge types in first graders. On the other hand, this missing correlation additionally supports the findings of Canobi et al [ 19 , 44 ] or Haider et al [ 48 ] who found first measureable integration of procedural and conceptual commutativity knowledge in second or third graders. Therefore, to maximize the chance of finding a possible beneficial influence of our approximation task on integration of conceptual and procedural knowledge in Experiment 3, we tested whether our approximation task might affect conceptual knowledge in third graders.…”
Section: Methodssupporting
confidence: 86%
See 4 more Smart Citations
“…On the one hand, this result suggests that our approximation task is not suitable to boost the integration of both knowledge types in first graders. On the other hand, this missing correlation additionally supports the findings of Canobi et al [ 19 , 44 ] or Haider et al [ 48 ] who found first measureable integration of procedural and conceptual commutativity knowledge in second or third graders. Therefore, to maximize the chance of finding a possible beneficial influence of our approximation task on integration of conceptual and procedural knowledge in Experiment 3, we tested whether our approximation task might affect conceptual knowledge in third graders.…”
Section: Methodssupporting
confidence: 86%
“…Thus, participants of Experiment 2 should not only be trained in solving addition problems, but also should have (at least) some formal conceptual knowledge about commutativity (see for example [ 42 ]). In order to assess conceptual knowledge, we used the above mentioned judgment task ([ 48 ]; Table 1 ) as an additional task. It resembled the computation task as it contained 30 addition problems altogether; 18 of which formed 9 commutative pairs.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations